Need help from an expert?
The world’s top online tutoring provider trusted by students, parents, and schools globally.
The formula for the nth term of a geometric sequence is an = a1 * r^(n-1).
To prove this formula, we can use mathematical induction. First, we need to show that the formula holds for n = 1. In a geometric sequence, the first term is a1 and the common ratio is r. Therefore, when n = 1, the nth term is simply a1 * r^(1-1) = a1, which is the first term of the sequence. So, the formula holds for n = 1.
Next, we assume that the formula holds for some arbitrary value of n, say k. That is, ak = a1 * r^(k-1). We need to show that the formula also holds for n = k+1. The (k+1)th term of the sequence is given by ak+1 = ak * r. Substituting the value of ak from our assumption, we get:
ak+1 = a1 * r^(k-1) * r
= a1 * r^k
This is exactly the formula for the (k+1)th term that we wanted to prove. Therefore, by mathematical induction, the formula an = a1 * r^(n-1) holds for all positive integers n.
Another way to prove the formula is by using the formula for the sum of a geometric series. The sum of the first n terms of a geometric sequence is given by:
Sn = a1 * (1 - r^n) / (1 - r)
We can rearrange this formula to get:
a1 = Sn * (1 - r) / (1 - r^n)
Substituting this value of a1 in the formula for the nth term, we get:
an = Sn * (1 - r) / (1 - r^n) * r^(n-1)
Simplifying this expression, we get:
an = Sn * (1 - r^(n-1))
Using the formula for Sn, we can rewrite this as:
an = a1 * r^(n-1)
Therefore, the formula for the nth term of a geometric sequence is proved.
Study and Practice for Free
Trusted by 100,000+ Students Worldwide
Achieve Top Grades in your Exams with our Free Resources.
Practice Questions, Study Notes, and Past Exam Papers for all Subjects!
The world’s top online tutoring provider trusted by students, parents, and schools globally.